(untitled) (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2025)
Background: Tuberculosis, one of the oldest diseases known to mankind, is even today a leading cause of human suffering and loss of life in developing country like Bangladesh. According to the surveys, the estimated prevalence rates of bacteriologically confirmed TB and smear-positive TB are 287 and 113 for Bangladesh (2015-16) per 100,000 population over the age of 15years. Tubercular lymphadenitis is the commonest form of extra-pulmonary tuberculosis and most commonly cervical lymph nodes are affected. However, it mimics other pathological conditions like metastasis from other primary sites, reactive lymphadenitis, chronic non-specific lymphadenitis, lymphoma etc. Therefore, it is important that healthcare professionals are aware of tuberculosis in the head and neck region which can aid in early diagnosis with the help of simple investigations and subsequently patients can be managed promptly without delay. The aim of this study is to find out the clinical characteristics of involved cervical lymph nodes and demographic characteristics of the patients. Materials and methods : A prospective study was performed in 250 Bed General Hospital, Chattogram, Bangladesh from May to November 2022. All cases of swelling in the neck or cervical lymphadenitis selected for the study were initially given conservative treatment in the form of antibiotics and were reviewed after 2 weeks. If neck swelling persists FNAC, USG and in some cases biopsy were performed. Total 85 patients were enrolled. Results: Age of the patients ranged from 5 to 60 years with a mean of 25.6 years. Two third (67.7%) of the patients were female. Male: Female ratio was 1:2.1. More than half of the patients came from rural areas (53.8%) and from low socioeconomic conditions (58.5%). Most of the patients presented with unilateral (87.7%), multiple (82.3%), matted (68.6%) lymph nodes, <3cm diameter (54%), commonly in right side (57.9%). Abscess was found in 21.5% cases. Discharging sinus was found in 9.2% cases. Most commonly involved lymph node group was level V (59.4%) followed by level II (42.2%). Systemic features were found in 63.07% patients. Associated lung lesion was found in 3.1% cases. FNAC was found positive for tuberculosis in 83.9% cases. Conclusion: Early diagnosis and treatment is critical in reducing the overall prevalence. It is essential to have awareness regarding common presentations of cervical tuberculous lymphadenitis among the general population as well as healthcare professionals working in the resource poor primary and secondary level hospitals. Chatt Maa Shi Hosp Med Coll J; Vol.23 (1); January 2024; Page 90-94